Kontribusi Motivasi Kerja dan Insentif terhadap Kinerja Pamong Belajar di SKB Kota Padang - Dodi, Angre (Universitas Negeri Padang, 2016)
Based on the phenomenon in the field is seen that the performance of officials in SKB city of Padang is still a problem tutors poor performance of officials in lesson planning, lack of discipline officials in carrying out duties, poor performance of officials in the implementation of learning, low capacity of officials in mastering learning materials and lack of loyalty work pamong , This study aims to reveal: the contribution to the performance of work motivation SKB tutors in the city of Padang, the contribution to the performance incentive SKB tutors in the city of Padang, and the contribution of motivation and incentives together on the performance of tutors in SKB Padang. The research methodology used in this study is a quantitative method by using quantitative descriptive analysis approach. The population in this study were twenty five people and all sampled in this study. The data were analyzed using correlation techniques. Testing hypotheses using correlation and regression technique is simple and multiple regression assisted with SPSS version. The results showed: Work motivation to contribute to the performance of officials in the city of Padang SKB with the contribution of thirty-six point four percent. Incentives contribute to the performance of officials SKB Padang City with the amount of twenty-six point two percent. Motivation and incentives jointly contribute to the performance of officials in the city of Padang SKB fifty-five point two percent. It is clear that to improve the performance of officials is good and should ideally be done through motivation and incentives are adequate.